Rje btsun Rdo rje rnal ʼbyor ma Nā ro mkhaʼ spyod dbaṅ moʼi sgrub thabs, bsñen sgrub, sbyin sreg sogs ñer mkho chos tshan phyogs gcig tu bkod - Pha-boṅ-kha-pa Byams-pa-bstan-ʼdzin-ʼphrin-las-rgya-mtsho, 1878-1941 (s.n., 1969)
Collected rituals for propitiation and meditative identification with Khechari (a form of Vajrayogini propagated by Naropa); from the liturgy of the Gelukpa sect of Tibetan Buddhism.